Editorial: Building Trust in the Digital Economy - Campbell, Leith H. (Journal of Telecommunications and the Digital Economy, 2022)
This editorial comes in two parts: some remarks on government plans for the digital economy and the necessity of building trust; and a brief introduction to the papers in this issue.